MicroRNAs as outcome predictors in patients with metastatic colorectal cancer treated with bevacizumab in combination with FOLFOX - Kiss, I; Mlčochová, J; Součková, K; Fabian, P; Poprach, A; Halamkova, J; Svoboda, M; Vyzula, R; Slaby, O (Oncology letters, 2017)
Bevacizumab is a humanized anti-vascular endothelial growth factor monoclonal antibody, used in combination with a oxaliplatin-based chemotherapy in the treatment of metastatic colorectal cancer (mCRC). The aim of the present study was to identify microRNA (miRNA)-based predictive biomarkers of therapy response in order to avoid unnecessary and costly therapy to non-responding patients. High-throughput miRNA microarray profiling (Affymetrix miRNA array) was performed on a discovery cohort of patients with mCRC. The discovery cohort was (n=20) divided into either responding (n=10) or non-responding (n=10) groups of bevacizumab/5-flourouracil, leucovorin, oxaliplatin (FOLFOX) treatment according to Response Evaluation Criteria in Solid Tumors criteria. Validation of candidate miRNAs was performed on an independent cohort of 41 patients with mCRC using quantitative reverse transcription polymerase chain reaction. Normalized data were subjected to receiver operating characteristic and Kaplan-Meier analyses. In total, 67 miRNAs were identified to be differentially expressed when miRNA expression was compared between responding and non-responding patients to bevacizumab/FOLFOX treatment (P<0.05). A total of 7 miRNAs were chosen for independent validation, which confirmed significantly higher expression of miR-92b-3p, miR-3156-5p, miR-10a-5p and miR-125a-5p (P<0.005) in tumor tissue of responding patients compared with non-reponding patients. Using the combination of miRNAs, the present study identified responders to the therapy with sensitivity 82% and specificity 64% (area under the curve = 0.8015). In conclusion, 4 predictive miRNAs associated with progression-free survival (PFS) were identified in patients with mCRC treated with bevacizumab/FOLFOX. Following further independent validations, detection of these miRNA may enable identification of patients with mCRC who may potentially benefit from the therapy.
Keywords: predictive biomarker; progression-free survival; microRNA; metastatic colorectal cancer; bevacizumab